Acción colectiva de las mujeres y procesos emancipadores en América Latina y el Caribe. Una aproximación desde los casos de Cuba, Bolivia y Ecuador. - Perea Ozerin, Iratxe (El Colegio de México A.C., 2017)
The participation of women’s movements in processes of emancipation has been dealt with from the perspective of international relations, emphasizing analysis of the Latin American context. Following this line of research, this paper proposes a study of the effectiveness of this participation in processes that present different characteristics with regard to the incorporation of this social participation and to the nature of the social actors incorporated, in this case women’s movements. The paper focuses on the Cuban Revolution and the recent constituent processes in Bolivia and Ecuador